2014
DOI: 10.1111/clr.12438
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of artifacts induced by titanium, titanium–zirconium and zirconium dioxide implants in cone‐beam computed tomography

Abstract: Zirconium dioxide implants generate significantly more artifacts as compared to titanium and titanium-zirconium implants. The intensity of artifacts around zirconium dioxide implants exhibited in average the threefold in comparison with titanium implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 21 publications
(24 reference statements)
5
70
0
8
Order By: Relevance
“…Another study compared different implant materials with regard to the appearance of artefacts in CBCT (Sancho‐Puchades et al. ). It was found that zirconium dioxide implants generate significantly more artefacts in comparison with titanium and titanium–zirconium implants.…”
Section: Resultsmentioning
confidence: 99%
“…Another study compared different implant materials with regard to the appearance of artefacts in CBCT (Sancho‐Puchades et al. ). It was found that zirconium dioxide implants generate significantly more artefacts in comparison with titanium and titanium–zirconium implants.…”
Section: Resultsmentioning
confidence: 99%
“…, Sancho‐Puchades et al. ). It is, therefore, controversial whether the peri‐implant tissue can accurately be assessed through this technique.…”
Section: Discussionmentioning
confidence: 99%
“…The values recorded for defect detection and classification by Hilgenfeld et al were generally slightly lower than ours. In their study, however, zirconia implants were used, which cause significantly more artifacts in CBCT than titanium ones (Sancho‐Puchades et al, ). Kühl et al recorded substantially lower values for defect detection and classification for titanium implants (Kühl et al, ).…”
Section: Discussionmentioning
confidence: 99%